NEWTON’S ABSOLUTE SPACE SUBSTANTIAL EXPANSION OF CONCEPTION - Rengifo Castañeda, Carlos Adolfo (Disertaciones, 2017)
In the Scholium on "Space and Time," Newton explains his concept referring to an absolute Space, which has existence as real as the physical bodies of others but independently of these, so one of the characteristics Newtonian physics will be the interest in granting a real and independent existence in space and time as well as to matter, since in Newton’s laws of motion is the concept of acceleration, and in this theory, the word acceleration can only denote "acceleration with respect to space." Therefore, Newton’s space should be conceived "absolute rest" or at least, so it is possible to consider the acceleration that appears in the laws of motion is a "magnitude" (or force), with some meaning. For this reason, we propose: "distinguish rest and both relative and absolute movement, for their properties, causes and effects."